Developing Subjectivity in Future Primary School Teachers - Zhurat, Yulya; Rudenko, Nina; Bekirova, Adile; Borovets, Olena; Doroshenko, Tеtiana; Skoryk, Tamara (My University, 2021)
The article formulates theoretical and methodological conditions for developing subjectivity in future primary school teachers in Ukraine. Therefore, it analyzes the Ukrainian experience of teacher training for primary school, as well as the aspects of the primary school teachers’ subjectivity in relevant scientific discourse. Besides, the article contains theoretical generalizations on the issue in question. Research methods include induction and generalization, prognostic methods in combination with modelling of principles of the educational process and sociological methods (used to identify students’ motivation towards teaching). The article proves that Ukraine as “a young democracy” must consider new conditions associated with significant socio-cultural, socio-economic and other changes in the society. It is so because they determine new requirements for the professional training of future primary school teachers. On the other hand, the analysis of relevant literary sources indicates insufficient attention to psychological, methodological, social and other aspects of teacher’s subjectivity. The authors of the article offer the updated definitions of key concepts on the development of teacher’s subjectivity. Also, they summarize theoretical and methodological principles of primary school teachers’ subjectivity in Ukraine and justify the new educational conditions for developing such subjectivity. The novelty of the research lies in its addressing the issue of developing subjectivity in future primary school teachers under the realities of Ukrainian education, which is still on the path of development.
Keywords: primary school teacher, motivational sphere, content updating, training modeling, humanistic philosophy of education, educational environment